2017
DOI: 10.1002/jemt.22971
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic investigations of palynological features of convolvulaceous species from arid zone of Pakistan

Abstract: The pollen morphology of some species of glamorous family Convolvulaceae from arid zones of Pakistan has been evaluated. The pollen grains were acetolyzed, measured, described qualitatively, and illustrated using Light microscopy and scanning electron microscopy (SEM). The examined species have differences in shape, size, polarity and exine ornamentation, confirming the eurypalynous character. The pollen types varies from psilate to echinate and colpi to tricolporate, tetracolporate and pantocolporate. Exine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

10
0

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 12 publications
2
55
0
1
Order By: Relevance
“…Additionally, SEM are a valuable research instrument that increasing our fundamental knowledge about previously unrecorded structural components of plants with high magnifications and resolution (Newton, ; Stant, ). Some previous studies (Ashfaq et al, ; Bahadur et al, ; Mannethody & Purayidathkandy, ; Moon, Hong, Smets, & Huysmans, ; Mousavi, Jafari, & Najafi, ; Salmaki et al, ; Ullah et al, ) also showed the importance of SEM in the identification, discrimination and phylogenetic relationship of other groups of plants.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, SEM are a valuable research instrument that increasing our fundamental knowledge about previously unrecorded structural components of plants with high magnifications and resolution (Newton, ; Stant, ). Some previous studies (Ashfaq et al, ; Bahadur et al, ; Mannethody & Purayidathkandy, ; Moon, Hong, Smets, & Huysmans, ; Mousavi, Jafari, & Najafi, ; Salmaki et al, ; Ullah et al, ) also showed the importance of SEM in the identification, discrimination and phylogenetic relationship of other groups of plants.…”
Section: Discussionmentioning
confidence: 90%
“…Exine often reticulate, microreticulate scabrate, and psilate are taxonomically significant features examined under SEM to identify monocot taxa at microlevel. Similarly, Ashfaq et al (), Bahadur et al (), Butt et al (), Kosenko (), Sufyan et al (), Ullah, Zafar, Ahmad, Dilbar, et al () investigated pollen of various taxa, using LM and SEM techniques and reported that the pollen morphological characteristics were of important characters for the taxonomic identifications of species and genera in different plant families. The LM and SEM study show variation between the species with special emphasis on exine ornamentation, which has a significant role to support the taxonomy of problematic and closely related taxa (Carrijo et al, ; Lopes, Andreata, Cartaxo‐Pinto, Trovó, & Gonçalves‐Esteves, ; Nurit‐Silva & De Fátima Agra, ).…”
Section: Discussionmentioning
confidence: 99%
“…Arid land vegetation is the important part of world's flora (Ashfaq et al ). Previously much work has been done on family Pontederiaceae, some work is also done on family Haloragaceae (Aiken, ; Cook, ), and some medicinal plants of family Mimosaceae has also been studied regarding palynology by Bhunia and Mondal () who also worked on Nymphaeaceae.…”
Section: Introductionmentioning
confidence: 99%